Aroma-triggered pain relief. (February 2018) - Lewis, Daniel; Tan, Cheemeng
Synthetic mammalian cells engineered to synthesize a painkiller in response to volatile spearmint reduce chronic pain in mice and do not seem to elicit adverse effects.